Targeted Therapies Compared to Dacarbazine for Treatment of BRAFV600E Metastatic Melanoma: A Cost-Effectiveness Analysis - Vanessa Shih; Renske M. ten Ham; Christine T. Bui; Dan N. Tran; Jie Ting; Leslie Wilson (Journal of Skin Cancer)
Purpose. Two BRAFV600E targeted therapies, dabrafenib and vemurafenib, have received US approval for treatment of metastatic melanoma in BRAFV600E patients, a mutation that affects ~50% of patients. We evaluated the cost-effectiveness of BRAF inhibitors and traditional chemotherapy for treatment of metastatic melanoma. Methods. A Markov model was developed using a societal perspective. Transition probabilities were derived from two Phase III registration trials comparing each BRAF inhibitor against dacarbazine. Costs were obtained from literature, national databases, and Medicare fee schedules. Utilities were obtained from published literature. Deterministic and probabilistic sensitivity analyses were run to test the impact of uncertainties. Results. The incremental cost-effectiveness ratio of dabrafenib was $149,035/QALY compared to dacarbazine. Vemurafenib was dominated by dabrafenib. Probabilistic sensitivity analysis showed that, at a willingness-to-pay (WTP) threshold of ≤$100,000/QALY, dacarbazine was the optimal treatment in ~85% of simulations. At a WTP threshold of ≥$150,000/QALY, dabrafenib was the optimal treatment. Conclusion. Compared with dacarbazine, dabrafenib and vemurafenib were not cost-effective at a willingness-to-pay threshold of $100,000/QALY. Dabrafenib is more efficient compared to vemurafenib. With few treatment options, dabrafenib is an option for qualifying patients if the overall cost of dabrafenib is reduced to $30,000–$31,000 or a WTP threshold of ≥$150,000/QALY is considered. More comparative data is needed.